Merging of synchrotron serial crystallographic data by a genetic algorithm. Issue 9 (1st September 2016) - Zander, Ulrich; Cianci, Michele; Foos, Nicolas; Silva, Catarina S.; Mazzei, Luca; Zubieta, Chloe; de Maria, Alejandro; Nanao, Max H.
Abstract : A genetic algorithm is described and used to select which sub‐data sets from a larger pool can be merged into a high‐quality data set. Abstract : Recent advances in macromolecular crystallography have made it practical to rapidly collect hundreds of sub‐data sets consisting of small oscillations of incomplete data. This approach, generally referred to as serial crystallography, has many uses, including an increased effective dose per data set, the collection of data from crystals without harvesting ( in situ data collection) and studies of dynamic events such as catalytic reactions. However, selecting which data sets from this type of experiment should be merged can be challenging and new methods are required. Here, it is shown that a genetic algorithm can be used for this purpose, and five case studies are presented in which the merging statistics are significantly improved compared with conventional merging of all data.